Relieving Pain in Oral Lesions of Pemphigus Vulgaris Using the Non-ablative, Non-thermal, CO2 Laser Therapy (NTCLT): Preliminary Results of a Novel Approach - Zand, Nasrin; Mansouri, Parvin; Fateh, Mohsen; Ataie-Fashtami, Leila; Rezaee Khiabanloo, Samad; Safar, Farid; Chalangari, Reza; Martits, Katalin; Shirkavand, Afshan (Journal of Lasers in Medical Sciences, 2017)
Introduction: Pemphigus vulgaris (PV) is a chronic, serious autoimmune mucocutaneous bullous disease. Oral lesions in PV may be extremely painful. This pain may adversely affect the patients’ oral intake and quality of life. This before-after clinical trial was designed to assess the pain relieving effects of single session of non-ablative, non-thermal CO2 laser therapy (NTCLT) in oral lesions of PV. Methods: Fifty painful oral lesions of fourteen patients with PV were illuminated by CO2 laser (power: 1 W, scanning the lesions with rapid circular motion of the handpiece) passing through a thick layer of transparent gel with high water content. The pain severity of the oral lesions was reported by the patients up to the fourth postoperative day. They were also asked to continue their existing systemic treatment during the course of this study as a precondition for the participation. Results: The severity of contact and non-stimulate (non-contact) pain declined immediately and significantly after NTCLT (P < 0.001). The pain relieving effect was sustained during the four successive days of follow-up. The procedure was pain free and no kind of analgesics was required. Following NTCLT, there were no visible thermal complications such as destruction, ablation or irritation of the oral lesions. Conclusion: The results of the trial proposed that single session of NTCLT could immediately and significantly relieve pain in oral lesions of PV, without any visible thermal complications.